Effect of HA content to the thermal behaviour and crystallinity of PCL/HA composite / Siti Zubaidah Abduljan - Abduljan, Siti Zubaidah (2018)
Polycaprolactone/hydroxyapatite (PCL/HA) composite is a hybridize bioactive inorganic particles which is one of the promising way in improving the mechanical properties with the strength brought by those ceramic, toughness with the bioactivity and osteoconductivity in tissue engineering. However, the present of HA may affect the crystallinity and heat properties of PCL/HA composite, where crystallinity and thermal properties of PCL/HA are very important and next foaming processing that is to create pore supercritical CO2. This crystallinity will affect the diffusivity of CO2 penetrate into PCL/HA composite. To reach the objective of this research, Thermogravimetric Analysis (TGA) used to investigate the effect of HA content in PCL/HA composite and Differential Scanning Calorimetry (DSC) to identify the crystallinity and thermal property of PCL/HA composite. In specifically studies on the character of PCL/HA, Fourier Transform Infrared (FTIR) was conducted to determine the functional group inside the PCL/HA composite. Besides that, sample that used in this study polymer is using the melt blending process at which may improve the homogenization of HA in PCL blend by ultrasonic wave. As a result, the pure PCL component degrades at 413.59ºC which clearly shows that PCL is completely degrade at 500ºC. As the high in HA content in the PCL/HA composites leads to decrease in crystallinity percentage because of the nucleation appear in the surface of the PCL composite.